Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/ci900382e
|View full text |Cite
|
Sign up to set email alerts
|

Combining Machine Learning and Pharmacophore-Based Interaction Fingerprint for in Silico Screening

Abstract: In this study, we developed a new pharmacophore-based interaction fingerprint (Pharm-IF) and examined its usefulness for in silico screening using machine learning techniques such as support vector machine (SVM) and random forest (RF) instead of similarity-based ranking. Using the docking results of PKA, SRC, cathepsin K, carbonic anhydrase II, and HIV-1 protease, the screening efficiencies of the Pharm-IF models were compared to GLIDE score and the residue-based IF (PLIF) models. The combination of SVM and Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 60 publications
0
123
0
Order By: Relevance
“…PLIFs are effectively a barcode for a particular protein:ligand complex, classifying interactions according to whether the interaction is mediated through the main chain or side chain, whether it is polar, non-polar or a hydrogen bond and whether the interaction is strong or weak (57). The frequency with which an interaction was predicted between citrate and a particular amino acid in the docking experiments was calculated from the PLIFs and is summarised in the heat maps presented in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…PLIFs are effectively a barcode for a particular protein:ligand complex, classifying interactions according to whether the interaction is mediated through the main chain or side chain, whether it is polar, non-polar or a hydrogen bond and whether the interaction is strong or weak (57). The frequency with which an interaction was predicted between citrate and a particular amino acid in the docking experiments was calculated from the PLIFs and is summarised in the heat maps presented in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…The method was successfully applied to study the SAR (Structure Activity Relationship) of 35 PDE-4 inhibitors. In another similar approach, atom based Interaction Fingerprint (IF) were applied to describe the patterns of ligand pharmacophores that interacted with proteins in complex [97]. These fingerprints are calculated from the distance of pairs of ligand pharmacophore features that interact with protein atoms delineating important geometrical patterns of ligand pharmacophores.…”
Section: Combination Lock and Keymentioning
confidence: 99%
“…MetaSite [161], as well. The advantages of using pharmacophoric models over conventional docking scoring functions are that pharmacophore provides versatility for any type of protein of interest and options to accentuate target-specific interactions, such as -orbital interactions and entropy effects [162].…”
Section: Structure-based Pharmacophore Modelingmentioning
confidence: 99%
“…Furthermore, Sato et al reported a new interaction fingerprint (IF) based on ligand pharmacophore (Pharm-IF) (Fig. 1c) [162]. Similar to residue-based PLIF developed by MOE, Pharm-IF is calculated from the distances of pairs of pharmacophore features which form interactions with protein [162].…”
Section: Structure-based Pharmacophore Modelingmentioning
confidence: 99%